Comparison of Effectiveness of Conventional Polypectomy with Functional Endoscopic Sinus Surgery: Conventional Polypectomy and Functional Endoscopic Sinus Surgery - Ullah, Asad; Zeb, Momina; Din, Wajih Ud; Mustafa, Sadaf Raffat; Babar, Mehveen; Arshad, Minahil (Pakistan Journal of Health Sciences, 2024)
It is common for rhinologists to face nasal polyposis. When other treatments have failed, patients must undergo Functional Endoscopic Sinus Surgery (FESS) with a microdebrider or traditional equipment to clear out their sinuses and restore normal airflow. Objective: To compare the effectiveness of conventional polypectomy with functional endoscopic sinus surgery in patients presenting to tertiary level care hospital in Islamabad, Pakistan. Methods: This study was conducted at Department of ENT Head and Neck Surgery, Pakistan Institute of Medical Sciences, Islamabad from November 2017 to December 2018. Eighty-eight patients were enrolled and they were randomly into group A and group B assigned for conventional polypectomy and functional endoscopic sinus surgery, respectively. Results: There were 27 (61.4%) males and 17 (38.6%) females and mean age was 34.59 ± 12.00 years in conventional polypectomy and 28 (63.6%) males and 16 (36.5%) females and mean age was 36.64 ± 10.76 years in function endoscopic sinus surgery. The recurrence rate after 6 months in patients underwent conventional polypectomy was 18 (40.9%) and functional endoscopic sinus surgery was 2 (4.5%). Conclusion: The frequency of recurrence of nasal polyps after conventional polypectomy was more than in patients receiving functional endoscopic sinus surgery procedure.